Baseline Assessment: Understanding WISE Freshman Students' Information Literacy Skills in a One-shot Library Session. Issue 3 (3rd July 2018) - Tran, Clara Y.; Miller, Carrie-Ann; Aveni, Doreen
ABSTRACT: To understand Women in Science and Engineering freshman student's information literacy skills, the authors surveyed seventy-five students with a pre- and posttest in a one-shot library session. The pretest received sixty-seven responses while the posttest received fifty-two responses. Although our survey tests did not show a significant difference in knowledge learned, they provided valuable insight into how much information students could obtain from a one-shot library session. Not surprisingly, a few students indicated that they preferred more library sessions to just one. The authors also discussed findings and identified areas in this one-shot library session that can be improved.